Optical and spectral characteristics of chromium ion doped double alkali-aluminum phosphates - Nedilko, S.; Gomenyuk, O.; Umanets, G.; Stus', N.; Slobodyanik, M.; Boyko, V.; Sheludko, V. (Functional Materials, 2005)
Diffuse reflection, luminescence, and luminescence excitation spectra of double alkalialuminum phosphate MAIP₂О₇ (M = Na, К, Сs) crystals doped with chromium ion have been considered. The reflection spectrum bands have been ascribed to excitation of Сг³⁺ ion in the crystal lattice. The luminescence spectra include two main bands lying in the green-orange and red spectral regions, respectively. Influence of the alkali metal cation on the "red" luminescence band position has been considered. The complex structure of the "green-orange" band has been shown to be due to superposition of the matrix intrinsic emission and extrinsic emission of chromium ions included in СгO²⁻ groups. The "red" luminescence band is caused by radiative transitions in Сг³⁺ ions being in octahedral oxygen environment. Influence of the crystal field, alkali cation type, and the crystal structure type on its spectral characteristics has been discussed. Проведено аналiз спектрiв дифузного вiдбивання, характеристик люмiнесценцii та її збудження кристалiв подвiйних фосфатiв лужного металу та алюмiнiю ряду MAIP₂О₇ (M = Na, К, Сs) легованих iонами хрому. Смуги у спектрах вiдбивання пояснюються як такi, що зумовленi збудженням iонiв хрому Сг³⁺ у гратцi кристала. Спектри люмiнесценцii складаються з двох основних смуг, якi знаходяться у зелено-оранжевiй та червонiй областях спектру вiдповiдно. Розглянуто вплив типу катiона лужного металу на положення "червоноi" смуги люмiнесценцii. Показано, що складна структура "зеле-но-оранжевоi" смуги люмiнесценцii зумовлена суперпозицiею власного свiчення матрицi кристала та домiшкових iонiв хрому, що входять до складу групи СгO²⁻. "Червону" смугу люмiнесценцii зумовлено випромiнювальними переходами в iонах Сг³⁺ в октаедричному кисневому оточеннi. Розглядається вплив кристалiчного поля, типу катiонiв лужного металу та структурного типу кристала на його спектральнi характеристики. Проведен анализ спектров диффузного отражения, характеристик люминесценции и ее возбуждения кристаллов двойных фосфатов щелочного металла и алюминия ряда MAIP₂О₇ (M = Na, К, Сs) легированных ионами хрома. Полосы в спектрах отражения обусловлены возбуждением ионов хрома Сг³⁺ в решетке кристалла. Спектры люминесценции состоят из двух основных полос, которые расположены в зелено-оранжевой и красной областях спектра, соответственно. Рассмотрено влияние типа катиона щелочного металла на положение "красной" полосы люминесценции. Показано, Что сложная структура "зелено-оранжевой" полосы люминесценции обусловлена суперпозицией собственного свечения матрицы кристалла и примесных ионов хрома, которые входят в состав группы СгO²⁻. "Красная" полоса люминесценции обусловлена излучательными переходами в ионах Сг³⁺ в октаэдрическом кислородном окружении. Рассматривается влияние кристаллического поля, типа катионов щелочного металла и структурного типа кристалла на его спектральные характеристики.